Development, validation, and effectiveness of animated video lessons for Grade 10 Science - Chavez, Jenny P.; Buenviaje, Rudy F. (2025)
The development of effective science intervention materials has been a focus of research aimed at addressing leaming gaps and improving student performance. This research investigated the effectiveness of video-based intervention materials in enhancing the competencies of Grade 10 Science learners at Southville 8C National High School in the Philippines during the school year 2024-2025. The study employed an experimental research design, utilizing two experimental groups exposed to the developed video lessons and one control group continuing with traditional teaching methods. Pre- and post-tests were administered to all groups, with the intervention period for the experimental groups occurring between assessments. The intervention materials were tailored to address the least mastered learning competencies identified from the first-quarter exam results. Analysis of the post-test results revealed significant improvements in mean scores for all groups, with the experimental groups exhibiting notably higher gains than the control group. This disparity underscored the effectiveness of the video-based supplementary learning materials when used alongside traditional teaching methods. Qualitative feedback from both students and teachers further supported the positive impact of the video lessons. Students found the lessons engaging, clear, and helpful in understanding complex concepts, appreciating the interactive elements and the ability to review the material. Teachers highlighted the accessibility, consistency, and ease of integration of the video lessons into their existing teaching schedules. The study concludes that video-based instruction is a valuable tool for improving science education, particularly in addressing leaming gaps and enhancing student engagement. Based on these findings, it is recommended that school
b